Prognostic significance of MRD and its correlation with arsenic concentration in pediatric acute promyelocytic leukemia: a retrospective study by SCCLG-APL group - Zhong Fan; Liang-Chun Yang; Yi-Qiao Chen; Wu-Qing Wan; Dun-Hua Zhou; Hui-Rong Mai; Wan-Li Li; Li-Hua Yang; He-Kui Lan; Hui-Qin Chen; Bi-Yun Guo; Zi-Jun Zhen; et al. (Therapeutic Advances in Hematology)
Background: Treatment outcomes for acute promyelocytic leukemia (APL) have improved with all-trans-retinoic acid and arsenic trioxide, yet relapse remains a concern, especially in pediatric patients. The prognostic value of minimal residual disease (MRD) post-induction and the impact of arsenic levels during induction on MRD are not fully understood. Objectives: To evaluate the relationship between post-induction MRD levels and relapse-free survival (RFS) in pediatric APL patients, and to investigate the correlation between blood arsenic concentration levels during induction therapy and MRD status. Design: A retrospective analysis of pediatric APL patients enrolled in a clinical trial from September 2011 to July 2020. Methods: We assessed the relationship between RFS and post-induction MRD levels using the log-rank test. The optimal MRD cut-off was determined using the “surv_cutpoint” function in the survminer R package. Arsenic concentration levels were monitored in 16 patients on days 7 and 14 of induction therapy, and Spearman correlation was used to analyze the relationship between arsenic concentrations and MRD levels. Results: Among 176 pediatric APL patients, with a median follow-up of 6 years, 4 relapsed. Patients with MRD >3.1% had significantly lower RFS compared to those with MRD ⩽3.1% (94.6% vs 100%, p = 0.023). In addition, a negative correlation was found between blood arsenic concentration levels and post-induction MRD levels. Lower arsenic concentrations were associated with higher MRD levels, with significant correlations observed for trough concentrations ( R = −0.666, p = 0.005) and peak concentrations ( R = −0.499, p = 0.049) on day 7. Conclusion: Our study highlights the prognostic significance of post-induction MRD assessment in pediatric APL. We also demonstrate a negative correlation between blood arsenic concentration levels and MRD, suggesting that lower arsenic concentrations during induction therapy may contribute to a higher MRD burden. These findings may inform strategies to optimize treatment and improve outcomes in pediatric APL. Trial registration: www.clinicaltrials.gov (NCT02200978).